Bilateral Anterior Fracture-Dislocation of Shoulder Joint- A rare case with Delayed Presentation - Sunku, Nithin (J Orthop Case Rep, 2012)
INTRODUCTION: The shoulder is the most frequently dislocated joint. Bilateral glenohumeral dislocations are rare and almost always posterior. Bilateral anterior fracture dislocations of humeral neck in a patient with seizure are extremely rare. We report one such case of delayed presentation of bilateral anterior fracture dislocation of shoulder after an epileptic attack. CASE REPORT: We describe a rare case of 30 year old gentleman who presented with first episode of seizure following alcohol withdrawal. Physical examination and radiographic assessment revealed fracture dislocation of bilateral proximal humeri (4 part fracture on right side and two part fracture on left). Patient presented 20 days after injury during which he was treated by local osteopath by immobilization and massage. Open reduction and internal fixation with simple T plate was done on right side and multiple K - wires were used on left side. At one year follow up the patient had acceptable range and was able to carry out daily activities. CONCLUSIONS: Bilateral anterior fracture dislocation of shoulder behave similar to unilateral fracture dislocations and treatment needs to be planned appropriately. Even in cases with delayed presentation good results can be achieved